If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -4) + x = -9(5 + -1x) Reorder the terms: 2(-4 + x) + x = -9(5 + -1x) (-4 * 2 + x * 2) + x = -9(5 + -1x) (-8 + 2x) + x = -9(5 + -1x) Combine like terms: 2x + x = 3x -8 + 3x = -9(5 + -1x) -8 + 3x = (5 * -9 + -1x * -9) -8 + 3x = (-45 + 9x) Solving -8 + 3x = -45 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -8 + 3x + -9x = -45 + 9x + -9x Combine like terms: 3x + -9x = -6x -8 + -6x = -45 + 9x + -9x Combine like terms: 9x + -9x = 0 -8 + -6x = -45 + 0 -8 + -6x = -45 Add '8' to each side of the equation. -8 + 8 + -6x = -45 + 8 Combine like terms: -8 + 8 = 0 0 + -6x = -45 + 8 -6x = -45 + 8 Combine like terms: -45 + 8 = -37 -6x = -37 Divide each side by '-6'. x = 6.166666667 Simplifying x = 6.166666667
| 3x1/5= | | 36c^2-(a^2+14ab+49b^2)=0 | | 8x+9-3x+12=14-7x | | N/2=30/10 | | v^2-7v-12=0 | | 2(n-6)+n=-36 | | 7x+4+7x+4-4+(7x+4)2=180 | | (1=7i)/(-5-i) | | 1/(-5-i) | | 3=-2a+7 | | 7/3z-1/4=5 | | x+1.5-0.5x=45 | | -2(y+3)+8=4y-2 | | 4(2y-8)-3y=-17 | | 2x-1=100 | | 85.5=9(m+3.2) | | 3(x-2)+1=2+4x | | 3/3v | | 4(x-3)=-8(x+1) | | s/13=4 | | [-1,2],y=1/2x-3 | | 45+x=x | | -19=6w+4w | | -19-1m=8(1+1m) | | -2(3a+5)=-46 | | -5(3u-4)+6u=3(u+8) | | 9/7=z/2 | | 10-x+7=20 | | 3/14(6/13) | | 7-8=13 | | 9x^2-8x+1=-x^2-2 | | 7(y+4.5)= |